Review of Methods for Improving the Cyclic Stability of Li–Air Batteries by Controlling Cathode Reactions. Issue 4 (5th February 2014) - Zhao, Ning; Li, Chilin; Guo, Xiangxin
Abstract The rechargeable Li–air battery (as well as the Li–O2 battery) is a promising candidate for energy storage applications, especially in application of electrical vehicles. However, many technical obstacles such as the limited cyclic stability, low electrical energy efficiency, and poor rate capability must be solved prior to its practical use. In this review, we focus on methods for extension of the cycle lifetime by controlling the key operation parameters. The important influence of working parameters on the cycle operation and the underlying mechanism related to cathode reactions are addressed. It is demonstrated that battery technology in combination with knowledge of the cathode material characteristics is essential for improvement of battery performance. Prospective utilization of battery technology for overcoming other problems of Li–air batteries is also discussed.